Pacífico FL 15 and Golfo FL 16, multi-environmental varieties of rice with extra long grain for Mexico - Hernández Aragón, Leonardo; Tavitas Fuentes, Leticia; Álvarez Hernandez, Juan Carlos; Tapia Vargas, Luis Mario; Ortega Arreola, Rubén; Esqueda Esquivel, Valentín; Jiménez Chong, José Alfredo; López López, Rutilo (Revista Mexicana de Ciencias Agrícolas, 2019)
During the 2012-2015 they were selected, biometrically evaluated, purified and morphologically characterized in plant and grain the rice lines FL07562-7P-3-3P-2P-M-150pZa-250pZa-0Za and FL08224-3P-2-1P-3P-M-150pZa-250pZa-0Za. Due to its high and stable yield potential, both in the Pacific slope and the Gulf of Mexico, in 2016 it was proposed to be released and registered with the National Seed Inspection and Certification Service (SNICS) as new varieties Pacífico FL15 (registry ARZ-026-010716) and Golfo FL 16 (registry ARZ-025-010716), and in 2018 they were assigned the numbers 1871 and 1872 of breeder’s title, respectively. Both varieties are resistant to the sogata-VHB complex (white leaf virus) and the endemic ‘rice burning’ disease (Pyricularia oryzae), and are moderately resistant to the new ‘spotted grain’ disease caused by Helminthosporium oryzae in association with others pathogens. The grain of both varieties is extra-long with excellent milling quality and good culinary quality. Basic seed was produced, and in October 2016 were delivered to the Mexican Rice Council, AC., 2.42 t of Pacífico FL 15 and 2.1 t of Golfo FL 16, and in the autumn-winter 2016-2017 began a program of production of registered and certified, seeds for planting in the rice areas of the Pacific Ocean slope and in the plains of the Gulf of Mexico. With these varieties, the rice growers will be able to contribute with 300 000 t of extra-long-grain rice demanded by the population.
Keywords: Oryza sativa L., FLAR, industrial quality, seed, yield stability.